PTH-210 Using quality improvement methodology can easily achieve savings in parenteral nutrition wastage. (22nd June 2015) - Allan, P; Ramu, A; Taylor, M; Guest, C; Harris, C; Blackett, B; Harper, L; Farrer, K; Abraham, A; Teubner, A; Lal, S
Abstract : Introduction: Parenteral nutrition (PN) cost ∼£80 per day to provide. Wastage of PN is high due to sudden changes in the clinical condition of the patient, loss of venous access or for organisational reasons. In healthcare settings improvement in patient quality of care at low cost yet that also achieves savings in provision of patient care is imperative to increase the quality of care available to other patients. We undertook a quality improvement project to reduce PN wastage by 10% in 9 months. Method: Quality Improvement (QI) project was carried out at a national Intestinal Failure Unit (IFU) to reduce waste in provision of in-patient PN. Using QI methodology we developed a SMART objective of reducing PN wastage by 10% in 9months. We drew up an appropriate driver diagram of primary and secondary drivers for PN wastage. We recorded reason for wastage and using a pareto chart determined the most likely cause of waste to target change. Using Plan, Do, Study, Act (PDSA) cycles we activated a number of different strategies to reduce wastage. We mapped changes in the main 7 categories for waste using i-charts and g-charts. Balancing charts were also used to ensure that any intervention did not have a negative impact on quality provision of care on the IFU. We compared waste between IFU to Nutrition Support Teams in Salford and in Oxford. Results: Baseline wastage over 12 weeks suggested 1000 bags per annum (p.a.) wastage. Using the following PDSA cycles we achieved a 39% reduction in PN wastage in 9 months, exceeding the proposed 10% and saving the unit ∼£35000. PDSA cycles used: Team awareness, regular highlighting of the problem, introducing it as a handover question, relabelling bags if not used whilst still within expiry date, stock rotation of stock bags, following a bag from fridge to patient, better coordination of discharge planning to prevent patients being at home when feed bags still available for them, splitting the fridge storage into days of the week so bags could be placed in correct day for each patient and if bags relabelled moved to the next available day, changing to standard bags during weaning process, taking patients off pre-ordering and changed to daily ordering to allow for altered discharge dates. Conclusion: PN wastage is common and costly – in a high use unit ∼£90000 p.a. Using appropriate driver diagram, concurrent PDSA cycles and a motivated team high levels of cost savings are possible with resulting quality improvement in patient care. Disclosure of interest: None Declared.